2021
DOI: 10.3390/w13202866
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanin Monitoring in Some Spanish Water Bodies with Sentinel-2 Imagery

Abstract: Remote sensing is an appropriate tool for water management. It allows the study of some of the main sources of pollution, such as cyanobacterial harmful algal blooms. These species are increasing due to eutrophication and the adverse effects of climate change. This leads to water quality loss, which has a major impact on the environment, including human water supplies, which consequently require more expensive purification processes. The application of satellite remote sensing images as bio-optical tools is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The relatively large 300 m spatial resolution of Sentinel‐3 imagery may also contribute to the underwhelming model performance for retrieval of all water quality variables. While Sentinel‐2 does not have the 620 nm band necessary to estimate phycocyanin concentrations directly, recent studies have successfully used Sentinel‐2 imagery to indirectly estimate phycocyanin (Beck et al., 2017; Pérez‐González et al., 2021; Sòria‐Perpinyà et al., 2020, 2021). The Sentinel‐2 models for phycocyanin and chlorophyll‐a select several of the same variables, yet the selection of several different algorithms for the phycocyanin model suggests a distinct statistical relationship between band reflectance and phycocyanin compared to chlorophyll‐a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively large 300 m spatial resolution of Sentinel‐3 imagery may also contribute to the underwhelming model performance for retrieval of all water quality variables. While Sentinel‐2 does not have the 620 nm band necessary to estimate phycocyanin concentrations directly, recent studies have successfully used Sentinel‐2 imagery to indirectly estimate phycocyanin (Beck et al., 2017; Pérez‐González et al., 2021; Sòria‐Perpinyà et al., 2020, 2021). The Sentinel‐2 models for phycocyanin and chlorophyll‐a select several of the same variables, yet the selection of several different algorithms for the phycocyanin model suggests a distinct statistical relationship between band reflectance and phycocyanin compared to chlorophyll‐a.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that Sentinel‐2 cannot sense the 620 nm phycocyanin absorption feature commonly used in phycocyanin retrieval, however, several studies have found success in using Sentinel‐2 based chlorophyll‐a proxy algorithms for indirect phycocyanin estimation (Beck et al., 2017; Pérez‐González et al., 2021; Sòria‐Perpinyà et al., 2020). Therefore, a combination of proxy algorithms, machine learning techniques, and feature selection methods is used to develop and assess models for phycocyanin and chlorophyll‐a retrieval based on Sentinel‐2 imagery.…”
Section: Methodsmentioning
confidence: 99%
“…In this study we analysed the algal and cyanobacterial blooms without specifying whether algae or cyanobacteria are the cause of the bloom. We used Sentinel-2 MSI data that are not as good for cyanobacteria observation as other satellite sensors, such as, Ocean and Land Colour Instrument onboard Sentinel-3 that has a spectral band at the wavelengths of 620 nm for detection of absorption of cyanobacteria-specific pigment phycocyanin [46]. Moreover, since more than half of lakes in the region are smaller than 1 km 2 we used data from a satellite with higher spatial resolution (Sentinel-2) as opposed to 300 m resolution Sentinel-3.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the launch of Sentinel-2 MSI (Multiple Spectral Instrument) and Lansat-8 OLI (Operational Land Imager) has provided the acquisition of data that could be comparable and with higher spatial resolution (10-60 m and 30 m, respectively), which is more adequate to monitor medium to small lakes and reservoirs [165][166][167][168]. However, the design of their imagery sensors was not originally thought for aquatic appli-cations and the lack of an orange band (~620 nm) has been challenging and has required the development of complex algorithms for PC estimation [169,170].…”
Section: Current Monitoring and Assessmentmentioning
confidence: 99%